The eastern crisis, 1875-1878, in British and Russian press and society - Phillips, James Peter (2012)
This thesis of 84,616 words uses the Eastern Crisis of 1875-78 to consider the Press in Great Britain and Russia. 5 case-study chapters consider respectively the reaction to the Bosnian and Hercegovinian revolt of 1875, the Bulgarian 'Atrocity Campaign' of 1876, the outpouring of public sympathy in Russia for the cause of the Serbs in 1876, the involvement of Greece in Eastern crisis, and the British 'Jingo' movement. For each case study, the relationship of the mass activity to the newspaper and periodical press is considered, as well as tracing the interplay between government and Press, and examining whether the Press was able to act as an intermediary between people and government. As this is a comparative study, these movements are considered not only through their own national Press, but through that of the other nation. A recurring theme throughout, is the running current of suspicion existing between Britain and Russia throughout this period, which is analysed in some detail, and shown to have been a highly significant factor in much of what was undertaken by both governments and individuals in Britain and Russia at this time.